Analisis Pembagian Kerja Pengelolaan Sumber Daya Alam Rumah Tangga di Pemukiman Rongsokan Melalui Kerangka Moser - Simanjuntak, Dian Jesica; Syawaldi, Farhan Pria; Sophia, Fransisca; Rangratu, Ona; Syafiq, Ridho; Anggraeni, Silviana Dwi; Hisyam, Ciek Julyati; Seruni, Mayang Puti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze how the division of labor in managing natural resources (NR) is socially constructed within household life in informal settlements. Using a qualitative approach and Moser’s gender analysis framework, the research examines how productive, reproductive, and community roles are performed and interpreted by family members. The findings reveal that women occupy a dominant position in managing domestic NR such as water, energy, and household waste due to their more consistent presence in the home, compared to men who work outside. Although women also participate in productive activities to support the household economy, their contributions are often not recognized equally. The study also finds that women face a double burden, having to carry out both productive and reproductive roles with minimal support from other family members. Furthermore, gender inequality is evident in men’s dominance over strategic decision-making and access to community-level resources. This study highlights that the division of labor in low-income households is not merely a technical arrangement but a socially constructed practice that reproduces gender inequality and structural burdens on women.